Femtosecond laser inscription and micromachining in novel flexible glass flat-fibre chips - Kalli, Kyriacos; Markos, Christos; Posporis, Andreas; Koutsides, Charalambos; Riziotis, Christos; Webb, Andrew Simon; Sahu, Jayanta Kumar S.; Holmes, Christopher H.; Gates, James C.; Smith, Peter George R. (My University, 2013)
We demonstrate femtosecond laser micro-machining and inscription of micro-optical structures, such as ring and disk resonators, Mach-Zender interferometers, and complex microfluidic devices, in a novel optical flat-fibre chip. In addition, we fill the channels with functional materials that can be used for sensing applications. Furthermore, direct write femtosecond-laser inscribed Bragg gratings are written in the Ge-doped flat-fibre core at 1547.8 nm. The flat-fibre chip offers a unique degree of freedom by allowing surface and sub-surface devices to be integrated onto an optical platform with the potential for straightforward incorporation into integrated photonic circuits or optofluidic devices.
Keywords: Bragg gratings; Femtosecond laser inscription; Flat fibre; Micro-optic devices; Optical fibres